Indian prevalence of familial hypercholesterolemia demystified by applying Dutch lipid clinic network criteria - Barde, Akshay Kacharu; Sethi, Sumit; Bhargav, Mohan; Waghdhare, Swati (International Journal of Advances in Medicine, 2022)
Background: Dyslipidemia is a growing problem in India, with familial hypercholesterolemia (FH) being an under diagnosed and under treated cause of the same. FH is a common genetic disorder associated with high LDL cholesterol, leading to premature CAD and peripheral vascular diseases. The prevalence of FH is 1 in 250 individuals. True global prevalence of FH is underestimated. The prevalence of FH in Indian population is still unknown. Methods: A total 4000 patients who had tested their lipid profile at Max hospital, between Aug 2017-Aug 2019 were screened. Out of these we found 530 patients with LDL cholesterol ≥155 mg/dl. Amongst these, 90 patients consented for clinic visit and examination, and thus enrolled and assessed for FH using the Dutch lipid clinic network (DLCN) criteria. Based on scores, patients were diagnosed as definite, probable, possible, or no FH. Other risk factors known to cause dyslipidemia such as smoking, diabetes mellitus and hypertension were excluded. Results: In a general population of 4000 patients, 4 individuals were detected with definite FH, showing a prevalence of 1 in 1000 (0.1%). Out of the enrolled 90 patients with high LDL cholesterol, 4 (4.44%) were diagnosed as definite, 14 (15.56%) as probable, 33 (36.67%) as possible, and 39 (43.33%) as unlikely FH. Conclusions: Prevalence of FH appears to be much higher among Indians with high LDL cholesterol. Therefore, it should not be ignored in individuals with high LDL cholesterol. To detect patients with FH, routine screening with simple DLCN criteria may be effectively used.